2023
DOI: 10.1007/s11524-022-00708-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Built Environment Factors and SARS-CoV-2 Infections at the Neighbourhood Level in a Metropolitan Area in Germany

Abstract: COVID-19-related health outcomes displayed distinct geographical patterns within countries. The transmission of SARS-CoV-2 requires close spatial proximity of people, which can be influenced by the built environment. Only few studies have analysed SARS-CoV-2 infections related to the built environment within urban areas at a high spatial resolution. This study examined the association between built environment factors and SARS-CoV-2 infections in a metropolitan area in Germany. Polymerase chain reaction (PCR)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In the UK and Germany, people spent more time in green spaces during the pandemic, considering them safe for socialising, physical activity, and recreation [56,57]. In Japan, there was a significant increase in pedestrian activities along the streets, city parks, peri-urban forests, and protected areas during the pandemic [58]. These studies highlight that green spaces can be visited safely during the pandemic.…”
Section: Discussionmentioning
confidence: 89%
“…In the UK and Germany, people spent more time in green spaces during the pandemic, considering them safe for socialising, physical activity, and recreation [56,57]. In Japan, there was a significant increase in pedestrian activities along the streets, city parks, peri-urban forests, and protected areas during the pandemic [58]. These studies highlight that green spaces can be visited safely during the pandemic.…”
Section: Discussionmentioning
confidence: 89%
“…Some studies have shown that living in more spacious apartments or in neighborhoods with higher levels of urban greenness was associated with lower COVID-19 infection rates [40]. The lockdown period has changed people's ways of living, working, and interacting in their living environments.…”
Section: Rethinking the Urban Environmentmentioning
confidence: 99%
“…The low relative risk in Rudow might also be a combination of the socio-economic situation (which is mostly classified as middle), the built structure, and population density. First studies have already investigated the relation between built structure and COVID-19 [92]. A well-designed regression analysis might be able to dissect the factors that lead to a lower relative risk in Rudow.…”
Section: Built Structuresmentioning
confidence: 99%